Integrating technology and instructional design to enhance educational practices (International Seven Journal of Multidisciplinary, 2024)
The Digital Age has brought significant challenges to education, requiring innovative approaches to keep students engaged and promote effective learning. This work aims to understand the role of instructional design in the transformation of educational practices, integrating technology to meet new learning needs. The methodology employed is based on a review of the literature on instructional design and its ability to improve the educational process. Instructional design is a field dedicated to creating effective learning experiences, involving needs analysis, goal setting, development of teaching strategies, resource selection, development of instructional materials, implementation, and evaluation. Continuous assessment is essential to identify areas for improvement and ensure that learning objectives are met. The integration of digital technologies in instructional design enhances the personalization of learning, promoting more dynamic and interactive environments. However, challenges such as teacher training, resistance to the adoption of new technologies, and digital inequality must be addressed. The conclusion points out that, despite these challenges, instructional design is a crucial tool for creating meaningful, inclusive, and accessible learning experiences. For its transformative potential to be realized, it is essential that educational policies guarantee equal access to the internet and technological tools. Furthermore, the incorporation of instructional design must be integrated into the skills and disciplines crucial for the 21st century, adapting to contemporary realities and promoting a more inclusive and effective education.